Computer applications in eco-efficiency assessment in logistics = Aplikacje komputerowe w ocenie ekoefektywności systemów logistycznych - Burchart-Korol, Dorota; Czaplicka-Kolarz, Krystyna (Zielona Góra: Faculty of Economics and Management Press)
The goal of this study is to present computer applications in eco-efficiency assessment in Logistics based on Umberto for Eco-efficiency software. The study defines the major components of eco-efficiency analysis like: Life Cycle Assessment (LCA) and Material Flow Analysis (MFA).
Keywords: oprogramowanie - Umberto for Eco-efficiency; systemy logistyczne; analizy przepływu materiałów (MFA); Ocena Cyklu Życia (LCA); ekoefektywność; Umberto for Eco-efficiency; logistics; Material Flow Analysis; life cycle assessment (LCA); eco-efficiency